TINJAUAN PELAKSANAAN PERMAINAN KECIL DALAM PROSES BELAJAR MENGAJAR PENJASKES SISWA DI SDN 233/VI SUNGAI HITAM II KECAMATAN JANGKAT - Astra, Sumarlim; Ismi Mori Saputra, Deka (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
Abstract This research is a descriptive study which aims to describe the implementation of small games in the teaching and learning process of students at SDN 233/VI Sungai Hitam II Jangkat District. This research started from a problem, namely that there are still many teachers who do not provide learning in the form of a series of small games. Because sometimes the lessons provided from warm-up to core activities are only monotonous and stiff movements, which can cause boredom and boredom for students. The population in this study were students in classes VA, VB, and VC at SDN 233/VI Sungai Hitam II,ANGKAT District, totaling 85 people. In this study, samples were taken of 20% of the population of students in classes VA and VB at SDN 233.VI Sungai Hitam II Jangkat District, namely 22 students. The sampling technique is Strafied Random Sampling. This research uses data collection techniques using a research instrument questionnaire using a Likert scale, with 5 alternative answers, namely strongly agree (SA), agree (A), doubtful (D), disagree (D), and strongly disagree (SD). The results of the research can be concluded that from the results of data analysis and descriptions regarding the review of the implementation of small games in the teaching and learning process of physical education for students at SDN 233/VI Sungai Hitam II Jangkat District, the motivation sub-variable was classified as good with an average gain of 3.28 or 65.78% . The qualification sub-variable was classified as sufficient with data acquisition with an average of 2.72 or 54.50%. Then the results of the facilities and infrastructure sub-variable were classified as adequate with data acquisition with an average of 2.81 or 56.32%. Keywords: motivation, Qualification, facilities and infrastructure